Menjamin Hak dan Kepastian Hukum Terhadap Orang Yang Berada Dalam Pengampuan - Amanda, Niken Dwi; Nurdin, Merry Kurniawati; Zahra, Hilyah Az; Malik, Syaiful; Akbar, Soultan Raffly; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2024)
Guardianship is a legal mechanism to place an adult who is deemed incapable of independent action, such as due to age, mental condition, or physical limitations, on the same status as children who are not yet capable of legal action. A guardianship order can be requested by the spouse, family, prosecutor's office, or any other interested party. The Surya Permana case is used as an example to show how judges consider evidence and the Respondent's condition before deciding on guardianship. In this case, the judge appointed the Respondent's wife as guardian to manage the Respondent's legal and financial interests. This research aims to provide a comprehensive understanding of the guardianship mechanism, the rights of guardians, the legal process involved, and the importance of legal protection for individuals under guardianship. In this research, the author uses a normative legal method that is descriptive in nature. The results of the study show that guardianship is an important legal instrument to guarantee the civil rights of individuals and prevent actions that harm themselves or others. The process of establishing guardianship is conducted through juridical and non-juridical considerations by the judge to ensure that the individual really needs guardianship. Guardianship can end if the individual's condition improves and he or she is deemed competent to perform legal acts.